O mito da desdolarização e a ascensão das moedas pequenas a moedas-padrão - Almeida, E. C. (Figuras & Negócios, 2023)
Abstract: Brief summary introduction: Since the North American dollar (US dollar or dollar) became the standard currency of international relations – especially after the end of gold having ceased to be the standard currency – many emerging countries have tried to take away from the dollar the mythical financial figure of “the only currency for sustained financial transactions”. Since the North American dollar (US dollar or dollar) became the standard currency of international relations – especially after the end of gold no longer being the standard currency – many emerging countries have tried to remove from the dollar the mythical financial figure of “single currency for sustained financial transactions”. An attempt was made to analyze whether de-dollarization is possible...